The influence of reward and leadership style on the extrinsic motivation among Royal Malaysian Police officers - Nor Liyana, Mohd Khalil (2015)
Most organizations are experiencing the challenges of understanding the factor that have significant and positive relationship on employees' motivation. The aim of this research was determine the relationship between reward, leadership style and extrinsic motivation among the 226 police personnel in IPD Kulim, Kedah. A questionnaire survey based on random sampling method was used to collect the data and data analysis was done using Pearson correlations and linear regression techniques to identify the relationship and test the hypothesis. The findings of this study indicate, that there is a significant and positive relationship between reward, leadership style and extrinsic motivation.